Association between cancer stigma and cervical cancer screening uptake among women of Dhulikhel and Banepa, Nepal. - Bandana Paneru; Aerona Karmacharya; Alina Bharati; Soniya Makaju; Bikram Adhikari; Dikshya Kafle; Sunila Shakya; Donna Spiegelman; Sangini Seth; Anne Stangl; Aamod Dhoj Shrestha; Archana Shrestha (PLoS ONE)
Background Cervical cancer ranks as the most common cancer among Nepalese women with a high incidence and mortality. Despite evidence that effective screening programs reduce disease burden, screening services are under-utilized. Cancer stigma can be a major barrier to cervical cancer screening uptake among Nepalese women. Objectives This study assessed the association between cancer stigma and cervical cancer screening uptake among women residing in semi-urban areas of Kavrepalanchok district (Dhulikhel and Banepa), Nepal. Methods We conducted a cross-sectional study among 426 women aged 30-60 years using telephone interview method from 15th June to 15th October 2021. A validated Cancer Stigma Scale (CASS) was used to measure cancer stigma and categorized women as presence of cancer stigma if the mean total score was greater than three. We obtained information on cervical cancer screening uptake through self-reported responses. Univariable and multivariable logistic regression were performed to assess the association between cancer stigma and cervical cancer screening uptake. We adjusted socio-demographic: age, ethnicity, occupation, religion and education, and reproductive health variables: parity, family planning user, age of menarche and age at first sexual intercourse during multivariable logistic regression. Results Twenty-three percent of women had cancer stigma and 27 percent reported that they had ever been screened for cervical cancer. The odds of being screened was 0.23 times lower among women who had stigma compared to those who had no stigma (95% CI: 0.11-0.49) after adjusting for confounders: age, ethnicity, occupation, religion, education, parity, contraceptive use, age of menarche and age at first sexual intercourse. Conclusion Women residing in semi-urban areas of Nepal and had cancer stigma were less likely to have been screened for cervical cancer. De-stigmatizing interventions may alleviate cancer stigma and contribute to higher uptake of cervical cancer screening.